Solve the system of linear equations below. y = -2x + 19 y = x + 7

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions.

A community for students.

Solve the system of linear equations below. y = -2x + 19 y = x + 7

Mathematics
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

\(y = -2x + 19 \\ y = x + 7\) so go for \(y = y\) ie: \( \ \ -2x + 19 = x + 7\) and see where you get
y=11? and x=4?
\(\large −2x+19=x+7 \) \(\large −2x+19 (+ 2x)=x+7 (+ 2x)\) \(\large 19=3x+7\) \(\large 19-7=3x+7-7\) \(\large 12=3x\) \(\large 3x=12\) \(\large \frac{3x}{3}=\frac{12}{3}\) \(\large x = 4\) check: \(y = −2(4)+19 = 11\) and \(y =(4)+7\ = 11 \) \(\huge \checkmark \)

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

awesome, thank you so much! i was a bit confused at first, you've helped greatly!

Not the answer you are looking for?

Search for more explanations.

Ask your own question